Nemesis the last days of the American Republic - Johnson, Chalmers A (New York : Metropolitan Books Henry Holt, 2008)
Prologue: The blowback trilogy -- Militarism and the breakdown of constitutional government -- Comparative imperial pathologies: Rome, Britain, and America -- Central Intelligence Agency: The president's private army -- U.S. military bases in other people's countries -- How American imperialism actually works: The SOFA in Japan -- Space: The ultimate imperialist project -- The crisis of the American Republic.
A Holt paperback
Originally published: New York : Metropolitan Books, 2006
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: United States -- Foreign relations,1989-.; United States -- Military policy; United States -- Politics and government,989-.